Strong and widespread cycloheximide resistance in Stichococcus-like eukaryotic algal taxa ... : مقاومة قوية وواسعة النطاق للهيكسيميد الحلقي في أصناف الطحالب حقيقية النواة الشبيهة بالمكورات الحلقية ... - Nur Hidayu Syuhada; Faradina Merican; Syazana Zaki; Paul A. Broady; Peter Convey; Narongrit Muangmai (OpenAlex, 2022)
This study was initiated following the serendipitous discovery of a unialgal culture of a Stichococcus-like green alga (Chlorophyta) newly isolated from soil collected on Signy Island (maritime Antarctica) in growth medium supplemented with 100 µg/mL cycloheximide (CHX, a widely used antibiotic active against most eukaryotes). In order to test the generality of CHX resistance in taxa originally identified as members of Stichococcus (the detailed taxonomic relationships within this group of algae have been updated since our study took place), six strains were studied: two strains isolated from recent substrate collections from Signy Island (maritime Antarctica) ("Antarctica" 1 and "Antarctica" 2), one isolated from this island about 50 years ago ("Antarctica" 3) and single Arctic ("Arctic"), temperate ("Temperate") and tropical ("Tropical") strains. The sensitivity of each strain towards CHX was compared by determining the minimum inhibitory concentration (MIC), and growth rate and lag time when exposed to ... : بدأت هذه الدراسة بعد الاكتشاف المصادف لثقافة أحادية الطحالب الخضراء الشبيهة بالمكورات الحلقية (Chlorophyta) المعزولة حديثًا من التربة التي تم جمعها في جزيرة Signy (أنتاركتيكا البحرية) في وسط نمو مكمل بـ 100 ميكروغرام/مل من cycloheximide (CHX، وهو مضاد حيوي يستخدم على نطاق واسع نشط ضد معظم حقيقيات النوى). من أجل اختبار عمومية مقاومة CHX في الأصناف التي تم تحديدها في الأصل على أنها أعضاء في Stichococcus (تم تحديث العلاقات التصنيفية التفصيلية داخل هذه المجموعة من الطحالب منذ إجراء دراستنا)، تمت دراسة ست سلالات: سلالتان معزولتان عن مجموعات الركائز الحديثة من جزيرة Signy (أنتاركتيكا البحرية) (" أنتاركتيكا "1 و" أنتاركتيكا "2)، واحدة معزولة عن هذه الجزيرة منذ حوالي 50 عامًا (" أنتاركتيكا" 3) والقطب الشمالي الفردي (" القطب الشمالي ")، والمعتدلة (" المعتدلة ") والاستوائية (" الاستوائية ") سلالات. تمت مقارنة حساسية كل سلالة تجاه CHX من خلال تحديد الحد الأدنى للتركيز المثبط (MIC)، ومعدل النمو وزمن التأخر عند التعرض لتركيزات CHX المختلفة. كانت جميع السلالات باستثناء "المعتدلة" شديدة المقاومة لـ CHX (الميكروفون > ...